Effect of different formulation of natural rubber and styrene-butadiene rubber blend on physical properties: article - Mohamad Roslee, Syafiq Adib; Sharudin, Rahida Wati; Mohamed, Rahmah (2019)
The demand for synthetic rubber is increasing every year. However, this petroleumbased product will have some harmful effects to the environmentt and air quality. Moreover, it can cause the depletion of petroleum resource. All this contribution has recently created an increase interest in natural base rubber with the use of renewable resources. Because of the problem this research was conduct to prepare the blend of natural rubber and styrene-butadiene rubber sample with different formulation. Then to study the effect of different formulation of natural rubber and styrene-butadiene rubber blend on the physical properties. For the preparation, natural rubber latex was clean and dry completely before going through mastication process to reduce the molecular weight of the rubber to make sure it dissolve easily in solvent. Styrene butadiene rubber was cut into small pieces and then dissolves in toluene and chloroform solution. The rubber was mix with 4 different formulations before been heat and dry overnight in the oven. Then the sample was prepare for testing using tensile tester. The speed was set to 500 mm/min .The speed was constant throughout the test to make sure same force was applied to all sample. The result shows that that blend of 50% of natural rubber with 50 % styrene-butadiene rubber has the highest value of tensile strength which was 1.145 MPa. While the highest tensile modulus for all formulation was sample with 80 % natural rubber and 20 % styrene-butadiene rubber. The value for all 3 tensile modulus was 0.38 MPa , 0.445 MPa and 0.66 MPa for M100 ,M300 and M500 respectively.